The concept of "normative power" of the EU as a factor in the successful development of integration processes in the Black Sea region - Mykola Popov (CES Working Papers, 2020)
The provision underlying the reforms in the EaP countries, the concept of "normative power" was supposed to ensure their preparation for integration into the EU. But the limited results of the European integration policy in the Black Sea region indicate that the adopted strategy does not meet the conditions prevailing in the world and the capabilities of the EaP countries. The conflict of interests of the key forces, the unwillingness of the EaP countries governments to actively implement the reform policy led to review the integration policy in the region. The analysis of problems includes consideration of the concept of external management and its application in the EaP countries, the main theories designed to justify the existing EU policy in the Black Sea and the assessment of the EU integration policy through the prism of Ukrainian reforms. The results of the research made it possible to offer recommendations for changing EU policies. The possibility of applying the proposed approach is considered on the example of such a special case as the participation of Ukraine in the integration "Black Sea Synergy" initiative.
Keywords: 330; normative power; European integration; reforms in EaP countries